DESENTISISASI OBAT - Selly Cintya Gusman; Raveinal Raveinal (Universitas Fort De Kock, 2020)
Giving drugs to some patients has the potential to experience side effects that can be life-threatening so doctors must provide alternative medicine to them. If the suspect's drug is not replaced by alternative medicine, drug desensitization can be carried out. Drug desensitization is a temporary induction of a state of tolerance to the drug. Although this therapy is only empirical, it is effective and with a better understanding of the mechanism of desensitization is expected to improve therapeutic methods. Considerations for determining desensitization protocols do not have to be rigid, they should follow a number of steps, namely patient evaluation aimed at finding the characteristics of adverse reactions in patients, determining the possibility of effective and safe fast drug desensitization, selecting appropriate protocols, gathering information about the patient's response to desensitization, and change the protocol as needed. Desensitization is said to be successful if the patient can complete up to the therapeutic dose and can tolerate repeated dosing until treatment is complete.